Passion in Sport Management Research: Looking Back to Move Ahead - Jiayao Qi; Marshall Magnusen; Samuel Y Todd (Journal of Applied Sports Management, 2024)
As a nearly “abused” term, passion is pervasive and distinctive concept in the sport industry. However, research about passion has often been limited to mainstream frameworks such as the dualistic model of passion, which was originally developed among sport participants (e.g., athletes) with survey-based research methods. Though helpful, this has created a gap between what the current literature offers and what is needed from contemporary passion research in sport management. Notably, more attention needs to be given to both sport job seekers and sport employees. Accordingly, in this piece, we look back on passion, covering its history, key theories, and relevant sport management studies in order to move ahead with an argument for greater exploration of work passion and how it can advance the study of passion in the professional realm of sport business.
Keywords: job seekers; management; organizational behavior; recruiting; sport employees